PERAN ULAMA PEREMPUAN DI ACEH (Studi Terhadap Kiprah Perempuan Sebagai Ulama di Kabupaten Bireuen dan Aceh Besar) - Muslim Zainuddin (Takammul : Jurnal Studi Gender dan Islam Serta Perlindungan Anak, 2017)
This article discusses about the role and position of women scholars in Bireuen and Aceh Besar district in order to see the progress and what areas could be run by women scholars and to look at some obstacles faced in carrying out that role. The goals are to obtain some important infor- mation about the presence of women scholars in both areas, with their certain characteristics. The method used in collecting data that is unstructured interviews with a number of women scholars and comparative study to identify some similar aspects and find the differences between the two districts as the basis of women scholars in Aceh. From the results of this study indicate that although the role and position of women clergy (ulama perempuan) has changed from year to year, but the recognition of the public still places men (Tgk agam) as the dominant figure of scholars in all fields. It is well understood as a social construction that apply fully in the two dis- tricts. Besides, for the women themselves do not have enough confidence to be called as "ulama perempuan". This condition in fact will affect the community recognition. Normally, some roles that are common done by ulama perempuan such as teaching, preaching, teaching rituals of Hajj and implementation burial (jenazah). Meanwhile, in the areas of writing and involved in religious organizations and political parties are still very seldom. It shown that the formation of ulama perempuan from the boarding itself, and the government even non-government parties still do not maximized. So it is needed some serious efforts through socialization and more at- tention later on.